Effect of the 5-lipoxygenase inhibitor ZD2138 on allergen-induced early and late asthmatic responses. - Nasser, S. M. (1994)
BACKGROUND--Leukotrienes are lipid mediators generated from arachidonic acid by the 5-lipoxygenase pathway which may play an important part in the pathophysiology of asthma. Previous studies have demonstrated attenuation of the allergen-induced early and late asthmatic responses by leukotriene receptor antagonists. The effect of the 5-lipoxygenase inhibitor ZD2138, a non-redox lipoxygenase inhibitor which inhibits leukotriene synthesis for 24 hours after single doses of 350 mg, on allergen-induced early and late asthmatic responses has been assessed. METHODS--Eight asthmatic subjects with baseline FEV1 > 70% were studied. On screening, all subjects developed an allergen-induced biphasic asthmatic response to grass pollen, cat dander, or house dust mite. ZD2138 (350 mg) or placebo was given on two occasions separated by two weeks in a randomised double blind fashion. Allergen inhalation challenge was performed four hours after dosing and FEV1 was measured for eight hours. The inhibitory activity of ZD2138 on the 5-lipoxygenase pathway was assessed by measurements of calcium ionophore-stimulated generation of LTB4 in whole blood ex vivo and by analysis of urinary LTE4 levels before administration of drug or placebo and at regular intervals after oral drug dosing and allergen challenge. RESULTS--ZD2138 produced no significant bronchodilatation or attenuation of the early or late asthmatic response, although there was 82% inhibition of whole blood generation of LTB4 in response to calcium ionophore stimulation and 52% reduction in urinary excretion of LTE4. CONCLUSIONS--In asthmatic subjects the 5-lipoxygenase inhibitor ZD2138 did not protect against allergen-induced asthmatic responses, despite substantial inhibition of 5-lipoxygenase.